Scale dependent nanomechanical properties of dentin adhesive and adhesive-collagen composite - Singh, Viraj; Parthasarathy, Ranganathan; Ye, Qiang; Spencer, Paulette; Misra, Anil (Frontiers in Dental Medicine, 2024)
The complex micrometer construct at the interface that joins the composite material to the tooth surface in restorative dentistry is composed of the composite formed by infiltrating adhesive into demineralized dentin (collagen matrix). The overall performance of composite restorations is therefore directly linked to the properties of the polymerized adhesive and adhesive-collagen composite. Nanoindentation and nanoDMA tests are performed on model methacrylate based adhesive and collagen-adhesive composite to study their mechanical properties. The adhesive collagen composite is prepared by the infiltration of dentin adhesive into a completely demineralized bovine dentin. The obtained experimental results show that both the neat adhesive and the collagen-adhesive composite are heterogeneous materials at the spatial scales of property interrogation. It is also found that the reduced elastic modulus generally decreases with increasing indentation contact depth reaching an asymptote for both neat adhesive and collagen-adhesive composite. This reduced modulus behavior can be attributed to the increase in the indentation interaction volume. In addition, the measured frequency dependent storage and loss moduli indicate that both the neat adhesive and collagen adhesive composites are viscoelastic materials which are likely to exhibit creep deformation and rate-dependent behavior in physiological function.